2012
DOI: 10.1002/nvsm.1417
|View full text |Cite
|
Sign up to set email alerts
|

Pictures of me: user views on their representation in homelessness fundraising appeals

Abstract: • There is a long-standing ethical debate regarding the 'right' representation of recipients in charity marketing materials that are intended to accurately define and represent social problems whilst also prompting the maximum response in voluntary income. The study presented in this article makes a contribution to that debate by highlighting the views of charity beneficiaries regarding their representation in fundraising campaigns. Drawing on data from five focus groups conducted in cities across England, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
58
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 40 publications
(60 citation statements)
references
References 25 publications
2
58
0
Order By: Relevance
“…The increasing competition in the sector is an important part of the reason why mass communication has become progressively more central to the operations of nongovernmental organizations (NGOs) for mobilizing funds and for securing support and legitimacy for their activities (Tester, ; Vestergaard, , p. 444). NGOs are increasingly forced to adopt “media logics” by selecting beneficiaries for fundraising campaigns guided by media (and political) agendas and focusing on the theatrics of giving (Moeller, ; Vaux, ; Vestergaard, , p. 511), including the use of shocking tactics to get their messages across (Breeze & Dean, ; Cohen, ; Holland, ) and adopting a “sound bite“ approach supported by negative images (Cohen, ; Holland, ; Lissner, ; Stride, ). A growing number of scholars have argued that such media logics may undermine organizations' trust and legitimacy (Hjarvard, ; Krotz, ; Vestergaard, ).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…The increasing competition in the sector is an important part of the reason why mass communication has become progressively more central to the operations of nongovernmental organizations (NGOs) for mobilizing funds and for securing support and legitimacy for their activities (Tester, ; Vestergaard, , p. 444). NGOs are increasingly forced to adopt “media logics” by selecting beneficiaries for fundraising campaigns guided by media (and political) agendas and focusing on the theatrics of giving (Moeller, ; Vaux, ; Vestergaard, , p. 511), including the use of shocking tactics to get their messages across (Breeze & Dean, ; Cohen, ; Holland, ) and adopting a “sound bite“ approach supported by negative images (Cohen, ; Holland, ; Lissner, ; Stride, ). A growing number of scholars have argued that such media logics may undermine organizations' trust and legitimacy (Hjarvard, ; Krotz, ; Vestergaard, ).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have found that charities often foster guilt or pity through their advertisements to donors for their cause and elicit responses that are believed to engender giving (Barnett & Hammond, ; Diamond & Gooding‐Williams, ; Doddington, Jones & Miller, ; Eayrs & Ellis, ; Hibbert, Smith, Davies & Ireland, ; Hung & Wyer, ; O'Dell, ; Small & Verrochi, ; Smith & McSweeney, ). Indeed, many studies find that dispositional empathy has positively influenced donors' behavior to give to someone they consider as “needy” such as donors giving more easily to victims of natural disasters than to those who they think might have become poor by their own “bad” choices (Bennett & Kottasz, ; Breeze & Dean, ; Hibbert et al ., ; Miller, ; Piferi, ; Zagefka et al ., ). These “needy” images attract donors by creating simplified, stereotypical images and fundraising messages focusing on broad “sellable” issues and a recognizable “face” (Breeze & Dean, ; Dean, ; Hibbert et al ., ).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations